(untitled) (Atti del Sodalizio Glottologico Milanese, 2018)
The current etymology of δελφίς connects it to δελφύς ‘womb; uterus’ and ἀδελφός ‘(co-uterinus) brother’, thus interpreting this name as ‘(sea animal) provided with a uterus’. The characterization of the dolphin as a sea-mammal, however, appears to belong to a scientific classification that emerges relatively late, with Aristotle. In the light of a wide series of comparanda among many IE languages (Old Irish, Latin, Germanic, Sanskrit etc.), I argue that the primary meaning of the IE root involved (*gʷelbh-) was ‘lip’ and that this denomination of the dolphin originally referred to its “long-lipped” snout (likewise several names of the swine, e.g. δέλφαξ), which coherently fits in with the frame of archaic, and also IE, folk-taxonomies. KEYWORDS: Greek, dolphin, etymology, meaning, folk-taxonomy